2008
DOI: 10.1021/bi801198m
|View full text |Cite
|
Sign up to set email alerts
|

Weak Coupling of ATP Hydrolysis to the Chemical Equilibrium of Human Nicotinamide Phosphoribosyltransferase

Abstract: Human nicotinamide phosphoribosyltransferase (NAMPT, EC 2.4.2.12) catalyses the reversible synthesis of nicotinamide mononucleotide (NMN) and inorganic pyrophosphate (PPi) from nicotinamide (NAM) and α-D-5-phosphoribosyl-1-pyrophosphate (PRPP). NAMPT, by capturing the energy provided by its facultative ATPase activity, allows the production of NMN at products/ substrates ratios thermodynamically forbidden in the absence of ATP. By coupling ATP hydrolysis to NMN synthesis, the catalytic efficiency of the system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
144
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(158 citation statements)
references
References 38 publications
(58 reference statements)
11
144
0
Order By: Relevance
“…The activation of NAMPT by ATP hydrolysis has suggested that phosphorylation on a conserved histidine is a common catalytic feature for the pyridine phosphoribosyltransferases (6,11,15). In the Fig.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The activation of NAMPT by ATP hydrolysis has suggested that phosphorylation on a conserved histidine is a common catalytic feature for the pyridine phosphoribosyltransferases (6,11,15). In the Fig.…”
Section: Discussionmentioning
confidence: 95%
“…presence of Mg 2ϩ and ATP, NAMPT undergoes a fast, near quantitative phosphorylation (6). Phospho-NAMPT is approximately 3 orders of magnitude more active than unphosphorylated enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations